Does Tax Evasion Affect Unemployment and Educational Choice? - Ann-Sofie Kolm; Birthe Larsen (Copenhagen Business School (CBS), Department of Economics, 2006)
While examining the macroeconomic effects of government tax and punishment policies, this paper develops a three-sector general equilibrium model featuring matching frictions and worker-firm wage bargaining. Workers are assumed to differ in ability, and the choice of education is determined endogenously. Job opportunities in an informal sector are available only to workers who choose not to acquire higher education. We find that increased punishment of informal activities increases the number of educated workers and reduces the number of unemployed workers. Considering welfare, we show it is optimal to choose punishment rates so to more than fully counteract the distortion created by the government's inability to tax the informal sector.
hdl:10398/7558
Keywords: H26; I21; J64; 330; Tax evasion; underground economy; education; matching; unemployment